MENINGKATKAN HASIL BELAJAR IPS POKOK BAHASAN KEBUTUHAN MANUSIA MELALUI PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY PADA SISWA KELAS VIIIE SMP NEGERI 3 KERTAK HANYAR TAHUN PELAJARAN 2015/2016 - Noraina Noraina (JURNAL SOCIUS, 2017)
The background of this research is based on poor learning outcomes of VIII-E Student in SMPN 3 Kertak Hanyar and also the wide gap between top and underachieving students. The objective of the research is to boost the learning outcomes of Social Science for Student of VIII-E SMPN 3 Kertak Hanyar through Implementing Two Stay Two Model. The research is done in two cycles including planning, implementation, observation, and evaluation. Performance indicator is if ≥ 80% students get Social Science scores ≥ 70 equivalent with KKM then the research is considered success. The first research cycle shows students with scores of Social Science above KKM is 13 students or 54, 17 %. Meanwhile student with scores below KKM is 11 students or 55, 83 %. This means the research must go to second cycle. Second cycle shows the result of students with scores above KKM is 20 students or 83,33%. Meanwhile students with scores below KKM is 4 students or 16,67%. This means total students with scores above the KKM is more than 80 % and meet the performance indicator. Te conclusion of the research is; the implementing of Two Stay Two Model is proven can boost the learning outcomes Student of VIII-E SMPN 3 Kertak Hanyar in Social Science topic Human Basic Needs. Specifically for class with wide gap and variety in students’ abilities where the top students can helps the underachieving students. It is suggested for Social Science teachers to using Two Stay Two Models in pedagogic activity for students who have wide gap capability where the top students can helps the underachieving students.Keywords: Learning Outcomes, Learning Model Two Stay Two Stray Latar belakang penelitian ini berdasarkan rendahnya hasil belajar IPS siswa kelas VIIIE SMP Negeri 3 Kertak Hanyar dan bervariasinya hasil belajar siswa, dimana ada siswa yang berkemampuan sangat tinggi sebaliknya ada siswa yang berkemampuan kurang. Penelitian tindakan kelas dilakukan dalam 2 siklus, meliputi perencanaan, pelaksanaan, pengamatan dan refleksi dengan indikator kinerja, yaitu jika sebanyak ≥80% siswa berhasil memperoleh hasil belajar  IPS ≥70, sesuai dengan KKM yang ditetapkan maka penelitian dianggap berhasil.Hasil penelitian siklus 1 menunjukkan siswa yang memperoleh nilai di atas KKM berjumlah 13 siswa atau 54,17%. Sedangkan siswa yang memperoleh nilai di bawah KKM sebanyak 11 orang atau 45,83%. Ini berarti banyaknya siswa yang tuntas KKM kurang dari 80% atau hanya 54,17% saja sehingga penelitian dilanjutkan ke siklus 2. Hasil penelitian siklus 2 menunjukkan hasil siswa yang memperoleh nilai di atas KKM bertambah jumlahnya menjadi  20 siswa atau 83,33%. Sedangkan siswa yang memperoleh nilai di bawah KKM sebanyak 4 orang atau hanya 16,67%. Ini berarti banyaknya siswa yang tuntas KKM lebih dari 80% dan sudah memenuhi indikator kinerja. Dengan menggunakan model pembelajaran Two Stay Two Stray terbukti dapat meningkatkan hasil belajar siswa kelas VIIIE SMP Negeri 3 Kertak Hanyar pada mata pelajaran IPS pokok bahasan Kebutuhan Hidup Manusia, khususnya pada kondisi kelas yang memiliki tingkat kemampuan kelas yang sangat bervariasi, sehingga siswa yang berkemampuan tinggi dapat diberdayakan untuk membimbing siswa yang berkemampuan kurang.Kata Kunci: Hasil Pembelajaran dan Model Pembelajaran Two Stay Two Stray